Peranan Camat dalam Mengkoordinir Peningkatan Pembangunan di Kecamatan Tiroang Kabupaten Pinrang - Andi Rauf (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2019)
Abstract This study aimed to determine the role of sub-district head in coordinating the development and improvement along with the influencing factors about development improvement at Tiroang District in Pinrang Regency. The population took 31 persons, consisted of 21 Tiroang District Office employees, the head of five (5) villages, and another five from the chairman of the village social institutions (EHS). The whole population were taken as samples, and as an informant was the secretary of Tiroang District. Data collection methods used were observation, questionnaires, interviews, and technical literature. The collected data was then analyzed by means of qualitative analysis techniques with a table percentage. The results showed that the role of district head as coordinator in improving the development of three sub-indicators were rated very well with a score of 3,40. Whereas the influencing factors, namely district head’s capability were rated very well with a score of 3,32, responsibility factor was also rated very well with 3,65, participation factor was rated 3,16, and finally excellent cooperation at 3,35 score.